1979
DOI: 10.1177/009579847900500203
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Speculations on Derogatory Names for Blacks

Abstract: The phenomenon of linguistic racism is explored through the application of the psychoanalytic theory of Joel Kovel's White Racism: A Psychohistory and the data of such analytic explorers as Kubie, Pinderhughes, Hamilton, and Grier and Cobbs. The psychodynamics of racism are related to the psychosexual development of the child and particularly to that phase encom passing toilet training with its conflicts, fears, and fan tasies. It is demonstrated that these psychological phenomena are corroborated by the socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…With respect to this, anthropologists have observed that &dquo;the use of symbols, in art as in language, implies a body of common understandings among the members of a society, and carries as well the implication that these understandings are transmitted from generation to generation&dquo; (Beals & Hoijer, 1965, p. 657). The play objects examined have insured the maintenance of beliefs that connote negative conceptions of African Americans (Baldwin, 1979;Banks, 1976;Kloss, 1979;Wilkinson, 1974). They further indicate that the images conveyed will continue to be sustained and transmitted from one generation to another (Wilkinson, 1971 ), since such images are part of our psychological history and our consciousness.…”
Section: Psychological and Cultural Implicationsmentioning
confidence: 84%
See 3 more Smart Citations
“…With respect to this, anthropologists have observed that &dquo;the use of symbols, in art as in language, implies a body of common understandings among the members of a society, and carries as well the implication that these understandings are transmitted from generation to generation&dquo; (Beals & Hoijer, 1965, p. 657). The play objects examined have insured the maintenance of beliefs that connote negative conceptions of African Americans (Baldwin, 1979;Banks, 1976;Kloss, 1979;Wilkinson, 1974). They further indicate that the images conveyed will continue to be sustained and transmitted from one generation to another (Wilkinson, 1971 ), since such images are part of our psychological history and our consciousness.…”
Section: Psychological and Cultural Implicationsmentioning
confidence: 84%
“…Operationally, attribution bias means that the subject is imputed to have particularistic features of an undesirable quality. This category designates the attributing of a &dquo;negatively affective&dquo; word or conception to a person or character (Kloss, 1979). Adjective bias is represented in the systematic creation of an impression by assigning adverse properties to a subject or an artifact (e.g., &dquo;mischievous pickaninny&dquo; for a Black baby doll).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A theme of this narrative is to construct parodies of White people. For (Kloss, 1979). White supremacy is unmasked as a survival tactic by a 'mutant, genetic deficient minority' (Welsing, 1991, pp.…”
Section: On the Offensivementioning
confidence: 99%